ANALISIS PENENTUAN HARGA POKOK PRODUKSI MENGGUNAKAN METODE FULL COSTING SEBAGAI DASAR PENETAPAN HARGA JUAL PADA UD. MUTIA MEUBEL - muda, markus; jitmau, fanny; Juliyanti, Eka Fiti (Jurnal Pitis AKP, 2021)
Calculation of the cost of production at UD. Mutia Meubel has not included depreciation costs for production machinery, building depreciation, vehicle depreciation costs and has not charged factory overhead costs. The company also reports that it is still very simple. The determination of the selling price is only based on a comparison with the market selling price and the desired profit every year is the same. This final project provides suggestions for determining the calculation of factory overhead costs, depreciation costs of production machines, depreciation of factory buildings, and vehicle depreciation costs. And it is necessary to apply a method of calculating the cost of production in accordance with the appropriate accounting standard method and the allocation of the elements of the cost of goods according to their function.